Pengembangan Kurikulum Berbasis Multi Pendekatan - Nur Fauzi (STAI Syaichona Moh. Cholil Bangkalan, 2020)
Abstract: There are five opinions of various approaches to curriculum development. First, according to Muhaimin there is divided into four types namely: Academicapproaches, humanistic, technological, and reconstructionis approaches.Secondly, according to Wina Sanjaya, it is divided into two approaches namely top-down and grass-roots approachesThirdly, according to H.M. Ahmad is divided into two approaches namely approaches thatare oriented towards subject matter, approaches that are oriented towards teaching objectives.Fourth, according to Zainal Arifin, it is divided into fifeapproaches, namely: competency, system, value clarification, comprehensive, and problem-centered approach.Fifth, according to Abdullah Idi, it is divided into threeapproaches, namely: approaches that are oriented to subject matter, material organization patterns, accountability.From various approaches, it can be concluded that the most widely used in developing curriculum is the student-oriented approach and the academic subject approach (oriented towards teaching material)